Análise da cultura da segurança entre os profissionais da unidade de terapia intensiva adulto de uma instituição de ensino - (:unkn) unknown (Universidade Federal de Goiás, 2016)
In recent decades, patient safety has aroused much concern and awareness in the world after scientific evidence of high mortality rates due to health care failures. The degree of complexity related to health care, especially in hospitals, requires specialized health management focused on quality and patient safety. This study aimed to evaluate the culture of patient safety the assets of the professional adult intensive care unit (ICU) in the Clinical Hospital of the Federal University of Uberlandia (HC-UFU), Brazil. The study was conducted in a cross exploratory study model in order to evaluate the culture of patient safety among professionals, with data collection in the period June-July 2016. The sample consisted of all professionals in the adult intensive care unit of the following areas: medical, nursing, physical therapy, psychology, nutrition, and management. This sample was applied to the Safety Attitudes Questionnaire (SAQ) as a tool in the assessment of patient safety culture. The analysis of statistical data and testing was performed using SPSS software (Statistical Package for Social Sciences for Windows) version 21.0. In the inferential analysis, we used the chi-square test (χ²), t-test and analysis of variance (ANOVA). The analysis adopted significance level (α) of 5%. The strength of association between variables was assessed by calculating the prevalence ratio (PR) (95%). A total of 163 permanent professionals in the adult ICU of the HC-UFU, 144 were active in their functions in the range on the collection and 138 SAQ questionnaires were validated by being properly filled, resulting in a validation rate of 96.5%. Most participants were female (76.1%) and had long experience ≥ 5 years (63.0%). The results of the SAQ noted an overall average of the safety culture in the ICU less than 75 points (57.80 ± 23.39). This result was detailed on an analysis of the areas and items without domains not strengthened findings, but with higher scores 60 to Working Climate team, Job Satisfaction, Stress Perception and collaboration among team members, and other below 50 for Hospital Management Perception, Work Condition and communication failures. It was concluded that the general perception of ICU for patient safety culture demonstrated weakening of all the attitudes of professionals and especially the actions of management. Since managers are responsible for determining human working conditions and freedom of communication between the errors, promoting gain knowledge without reprisal or warnings.
Keywords: Cultura; Segurança; Gestão de segurança; UTI; Cuidados críticos; Culture; Safety; Safety management; ICU; Critical care; OUTROS::ADMINISTRACAO HOSPITALAR